RISK FACTORS FOR ESTROGEN EXPOSURE IN VARIOUS GRADES OF ENDOMETRIOID CARINOMA - Ma’rifatu Ulfa Hidayati; Pungky Mulawardhana; Nila Kurniasari (UNIVERSITAS AIRLANGGA, 2020)
AbstractBackground: Incidence endometrial cancer in Southeast Asia it is estimated that 41% of new cases emerge. The incidence of endometrial cancer in Dr. Soetomo General Hospital has increased every year. In 2016 there were 119 new cases of endometrial cancer and in 2017 there were 160 cases. 75%-80% is type I endometrial cancer (endometrioid carcinoma). Risk factors for estrogen exposure (early menarche, parity, obesity) are risk factors for endometrial cancer. The prognosis of endometrial cancer depends on the grade. This study aims to determine differences in risk factors for estrogen exposure in various grades of type I endometrial cancer (endometrioid carcinoma) in the Poli Onkologi Satu Atap Dr. Soetomo General Hospital Surabaya. Methods: the research method was analytic observational with cross-sectional design. Sample size of 40 medical records was taken by total sampling technique. Research variables include age of menarche, parity, BMI, and grade of endometrial cancer. The instrument used was a data collection sheet and medical records. Data analysis using chi-square test. Results: The results showed 52% patients were grade 1-2, there were 95% of menarche patients in the age range of 12-14 years, 62.5% patients had parity of 1-2 and 52% patients, BMI was underweight-normal category. Test results based on early menarche did not show significant differences between grades 1-2 and grade 3 in endometrioid carcinoma (p = 0.168). Likewise, parity in various grades of endometrial cancer type I (endometrioid carcinoma) there was no significant difference (p = 0.220) and BMI also no significant difference (p = 0.987). Conclusions: risk factors for estrogen exposure which include menarche, parity, obesity do not make a significant differences to the grades of endometrioid carcinoma.